Factors and Impact of the Crime of Adultery on Family Unity and Children's Future - Gustiara, Nisa; Susanti, Emilia; Dewi, Erna (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to determine the causal factors and efforts to overcome the crime of adultery so that they can be taken into consideration by someone who is planning to commit the crime of adultery. This research is important because regulations regarding adultery are not yet a solution to prevent adultery, so this research was carried out to find out the criminological causal factors and find out prevention efforts. This research uses normative empirical methods, data collection was carried out through direct interviews with the Bandar Lampung police station to obtain data on crimes of adultery. This is because this research examines legal norms relating to adultery as a social "parasite". The results of the research show that law enforcement and non-penal measures have not had a deterrent effect on perpetrators of adultery, so regulations regarding the crime of adultery must be updated by increasing the number of penalties for perpetrators and closing locations that have the potential to become places of adultery.